Management of suboptimal response to induction chemotherapy in locoregionally advanced nasopharyngeal carcinoma: Re-induction therapy or direct to Radiotherapy?. (October 2021) - Liu, Ting; Liu, Li-Ting; Lin, Jie-Yi; Shen, Bo-Wen; Guo, Shan-Shan; Liu, Sai-Lan; Sun, Xue-Song; Liang, Yu-Jing; Luo, Mei-Juan; Li, Xiao-Yun; Chen, Qiu-Yan; Tang, Lin-Quan; et al.
Highlights: Re-induction therapy could not improve tumor control of subsequent radiotherapy. Re-induction therapy impaired locoregional relapse-free survival of nasopharyngeal carcinoma. Re-induction therapy impaired progression-free survival of nasopharyngeal carcinoma. Re-induction therapy increased grade 3–4 hematological toxicities. Abstract: Background: Unsatisfactory tumor response to induction chemotherapy (IC) is an adverse prognostic factor of locoregionally advanced nasopharyngeal carcinoma (LANPC). A re-induction strategy which applies additional cycles of an alternative IC regimen prior to radiotherapy (RT) has been adopted. Methods: A total of 419 LANPC patients who attained suboptimal response (stable disease or disease progression) according to the Response Evaluation in Solid Tumors (RECIST) guideline after initial IC were retrospectively included. They were divided into those who received additional cycles of re-induction regimen prior to RT (re-induction group, n = 87) and those who had no additional chemotherapy (direct to RT group, n = 332). Propensity score matching (PSM) was used to adjust for potential confounders. Tumor response and long-term survival were compared between two groups. Results: After receiving a second IC regimen, 39.1% of the patients in re-induction group attained partial response; however, the tumor control of subsequent RT was not significantly improved when compared with direct to RT group (patients attaining complete response after RT 55.2% vs. 52.5%, P = 0.757). Patients who received re-induction therapy showed worse locoregional relapse-free survival (LRFS) and progression-free survival (PFS) than those proceeded directly to RT (3-year LRFS 75.7% vs. 83.1%, P = 0.005; 3-year PFS 62.4% vs. 68.3%, P = 0.037). The increased hematological toxicities were observed in re-induction group that included grade 3–4 anemia, thrombocytopenia and liver enzyme increase. Conclusion: Re-induction therapy decreased LRFS and PFS and increased toxicities among patients who attain suboptimal response to initial IC regimen, as compared with direct to RT strategy.